Rancang Bangun Mesin Screw Extruder Pencetak Arang Briket - Hadi Santosa; Yuliati Yuliati (Universitas Trunojoyo Madura, 2023)
Efforts to use renewable energy in a sustainable manner aim to maximize the resources and potential of renewable energy as an alternative energy source and minimize the use of petroleum or fossil energy. One of the alternative energy sources in the form of biomass is bio briquettes. One of the technological stages of making bio briquettes is the process of compaction or densification of the briquette material. Based on this, the purpose of this research is to design a screw extruder machine for bio briquette printing. This tool is designed to be energy efficient, easy to operate and maintain. The research method used is the calculation and analysis of machine elements in the initial design of the tool, the design of materials / materials and the manufacture of bio briquette materials for testing tools in an effort to test the performance and technical specifications of the tool. The result of this research is that there are three stages of the bio briquette printing screw extruder, namely the feed section, compression section and metering section. The technical specifications are that this tool is primarily driven by an electric motor with a rotating speed of 1400 rpm and an electrical power of 2 HP, the V belt used is a trapezoid type A. The screw extruder has an extruder turning torque of 0.055 kg m and an extruder driving power of 0.042 HP. The output of this machine is continuous with a briquette capacity of 200 kg/hour.